2012
DOI: 10.1371/journal.pone.0031534
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Mammalian Type Opsin 5 Functions Dually in the Photoreceptive and Non-Photoreceptive Organs of Birds

Abstract: A mammalian type opsin 5 (neuropsin) is a recently identified ultraviolet (UV)-sensitive pigment of the retina and other photosensitive organs in birds. Two other opsin 5-related molecules have been found in the genomes of non-mammalian vertebrates. However, their functions have not been examined as yet. Here, we identify the molecular properties of a second avian opsin 5, cOpn5L2 (chicken opsin 5-like 2), and its localization in the post-hatch chicken. Spectrophotometric analysis and radionucleotide-binding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 47 publications
(64 reference statements)
0
46
0
Order By: Relevance
“…In our previous reports, we succeeded in the purification of recombinant Opn5 proteins obtained by the expression of chicken Opn5 genes and reported that these proteins are UVsensitive bistable pigments that activate the G i type of G protein (4,7). We also speculated from the complete conservation of the amino acid residues surrounding the chromophore between chicken and mammalian Opn5m proteins that mammalian Opn5m proteins should be UV-sensitive pigments, which was recently confirmed in mouse and human Opn5m proteins (8).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…In our previous reports, we succeeded in the purification of recombinant Opn5 proteins obtained by the expression of chicken Opn5 genes and reported that these proteins are UVsensitive bistable pigments that activate the G i type of G protein (4,7). We also speculated from the complete conservation of the amino acid residues surrounding the chromophore between chicken and mammalian Opn5m proteins that mammalian Opn5m proteins should be UV-sensitive pigments, which was recently confirmed in mouse and human Opn5m proteins (8).…”
mentioning
confidence: 87%
“…Opn5 is the most recently identified opsin in the human and mouse genomes (3) and is categorized in an independent group on the basis of its low sequence homology to the other opsin groups. Opn5 genes have been identified in various vertebrates from fishes to primates and are classified into several subgroups (4,5). Most mammals have only one Opn5 gene (Opn5m), whereas nonmammalian vertebrates have additional Opn5 genes.…”
mentioning
confidence: 99%
“…The function of OPN3 in mammals is unknown despite its widespread expression in neural tissues (18). OPN5 appears to be a deep-brain photopigment in the hypothalamus of birds and is thought to contribute to seasonal reproduction (19)(20)(21)(22); it has been immunolocalized to the mammalian inner retina (13, 16) (SI Text); however, to date, no retinal function for this mammalian pigment has been identified. We did not examine two other pigments, retinal G protein-coupled receptor (RGR) opsin (23) and peropsin (RRH) (24).…”
mentioning
confidence: 99%
“…To date, however, which sites are critical and how they communicate among themselves remain unknown. Each of the 4 neural loci proposed to house DBP is in different brain structures, and 3 distinct photopigments have been discovered and thought involved in the reception of photoperiodic information: melanopsin/Opn4 (Chaurasia et al, 2005;Kang et al, 2010), neuropsin/Opn5 Ohuchi et al, 2012), and vertebrate ancient opsin (VAOpn; Foster et al, 1985Foster et al, , 1994Halford et al, 2009;Davies et al, 2012).…”
Section: (1) Sensory Photopigment System Involves Deep-brain Photorecmentioning
confidence: 99%
“…Brains were removed rapidly, frozen, and the septal-hypothalamic regions were dissected into 3 regions: (R1) the septal, preoptic, anterior hypothalamic (SepPre/Ant-Hypo) region including the LSO and the lateral bed nucleus of the stria terminalis (BSTL; Figure 2B); (R2) the mid-hypothalamic (Mid-Hypo) region containing the PVN and a major group of GnRH-1 neurons surrounding the nucleus of the hippocampal commissure ( Figure 2B); (R3) the posterior hypothalamic (PostHypo) region containing the PMM and PVO, PT, and median eminence, Figure 2B). The reason for making the 3 dissections is that the first region includes the LSO and lateral septum with scattered neurons containing Opn4 (Chaurasia et al, 2005) and the BSTL with Opn5 neurons (Ohuchi et al, 2012). The MidHypo contains VAOpn (Halford et al, 2009) neurons in the PVN and medial bed nucleus of the stria terminalis.…”
Section: Multiple Brain Sites Containing Functional Dbpmentioning
confidence: 99%